(untitled) (Mongolian Journal of Agricultural Sciences, 2023)
The objective of this research was to determine the effect of the extended dry aging period (0, 20, 40, and 60 days) on lipid oxidation, fatty acid profile, and tenderness in selected dry aged Hanwoo cow beef cut loins. Dry aging regimes were 40C and 85% relative humidity. Lipid oxidation was determined by using 2-thiobarbituric acid reactive substances. Shear force values of the highly marbled beef decreased first 20d aging, and did not significantly change after that, until 60d. Hardness of texture profile analysis gradually decreased, but chewiness value did not differ. A total of 16 fatty acids were identified in dry-aged beef. The most predominant FAs in the aged beef were C18:1, C16:0, and C18:0. The C18:2 was the predominant polyunsaturated fatty acid in the samples. Total PUFA gradually and C18:2n-6 decreased (p<0.05) during aging. C20:1, C18:3n-3, C20:4 and C22:1 acid significantly decreased (p<0.05) until 20d aging and no changes were observed after 20d to 60d. 2-thiobarbituric acid reactive values of beef increased (p<0.001) during dry-aging days, dry aging for 40d and 60d resulted in excessive oxidation of lipids. Dry-aged meat is so popular because of its unique taste. Improvements in tenderness associated with the 20d aging of a beef subprimals, however, some lipid oxidation may be associated with the development of specific dry-aged beef flavor.